2021
DOI: 10.1038/s41598-021-84370-y
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of new Corvis ST parameters for detecting subclinical and clinical keratoconus eyes in a Chinese population

Abstract: This study aimed to compare the values of new corneal visualization Scheimpflug technology (Corvis ST) parameters in normal, subclinical keratoconus (SKC) and keratoconus (KC) eyes, and evaluate the diagnostic ability to distinguish SKC and KC eyes from normal eyes. One-hundred normal, 100 SKC and 100 KC eyes were included in the study. Corvis ST parameters containing dynamic corneal response parameters were measured by one ophthalmologist. The receiver operating characteristic curve was used to evaluate the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 39 publications
1
22
4
1
Order By: Relevance
“…It is worth mentioning though only few studies on Chinese keratoconus patients assessed the sensitivity and specificity values of the CBI when compared to the original publication and they showed similar results (30,31).…”
Section: Discussionmentioning
confidence: 91%
“…It is worth mentioning though only few studies on Chinese keratoconus patients assessed the sensitivity and specificity values of the CBI when compared to the original publication and they showed similar results (30,31).…”
Section: Discussionmentioning
confidence: 91%
“…Peris-Martinez et al [ 33 ] published that A2 speed was the best parameter to diagnose patients with subclinical keratoconus. In a recent study, Ren et al [ 34 ] demonstrated that ARTh and SP-A1 variables were lower in eyes with subclinical keratoconus than in normal eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was an essential variable in our regression model. In a recent study, Ren et al [28] showed that ARTh and SP-A1 variables were lower in SCKC eyes than in normal eyes. According to this study, SP-A1 had the highest accuracy in identifying SCKC from control eyes.…”
Section: Discussionmentioning
confidence: 93%